Adaptive Energy Conservation Model using Dynamic Caching for Wireless Devices - Mavromoustakis, Constandinos X.; Karatza, Helen D. (My University, 2004)
One important issue that has to be taken into accountin wireless devices is the energy conservation. Everyinfrastructureless network must be adaptively selfconfigured particularly in terms of energy, connectivity,and memory. Efficient utilization of battery power isimportant for wireless users because due to theirmovements their energy is fluctuating at different levelsduring operation mode. Traffic plays a major role forenergy consumption because of the unpredictableincoming-flow nature. This paper describes anadaptive method called Adaptive Dynamic CachingEnergy Conservation (ADCEC), which bounds anasynchronous operation where each node evaluatesdissimilar sleep-wake schedules/states based on eachnode's incoming sleep-history traffic. Simulation study iscarried out for the energy conservation evaluation of theproposed model taking into account a number of metricsand estimation of the effects of incrementing the sleeptime duration to conserve energy.